Treatment of juvenile rheumatoid arthritis - Kwang Nam Kim (Korean Pediatric Society, 2010)
The systematic approach to pharmacologic treatment is typically to begin with the safest, simplest, and most conservative measures. It has been realized that the more rapidly inflammation is under control, the less likely it is that there will be permanent sequelae. Nonsteroidal anti-inflammatory drugs (NSAIDs) are the mainstay of initial treatment for inflammation. In addition, the slow-acting antirheumatic drugs (SAARDs) and disease-modifying antirheumatic drugs (DMARDs) have efficacy of anti-inflammatory action in children with chronic arthritis. New therapeutic modalities for inflammation, such as etanercept and infliximab, promise even further improvements in the risk/benefit ratio of treatment. It is not typically possible at the onset of the disease to predict which children will recover and which will go on to have unremitting disease with lingering disability or enter adulthood with serious functional impairment. Therefore, the initial therapeutic approach must be vigorous in all children.